THE EFFECT OF VISUAL TRACKING EXERCISES ON SOME MOVEMENT ABILITIES AND THE SKILL OF DEFENDING THE COURT IN VOLLEYBALL FOR STUDENTS - Salah Hadi Hamad; Haneen Mohammed Saad; Baraa Ismail Agam; Mohammed Khamis Farhan (Proximus Journal Publishing, 2024)
One of the fundamental skills in volleyball is paying attention to visual workouts since, in great part, the game depends on sight. The study sought to create a series of visual exercises and ascertain how they would affect some motor skills as well as court defense ability. To fit this study and the nature of it, the researchers applied the experimental approach including one experimental group. issue, and these drills were implemented on a sample of thirty fourth-year College of Physical Education - Wasit University students. Following the completion of the primary trial, the researchers arrived to the most significant findings: the created visual exercises improved motor skills and ability by means of their favorable and efficient impact. One of the most crucial advice is to rely on such activities and on other examples at various ages since their relevance and influence on the level of learners in a good and effective way define the court in volleyball for students.
Keywords: Visual Tracking; Exercises; Movement Abilities